Effect of 0.05% chlorhexidine gluconate in water on the hydrophilic inflatable penile prosthesis: biocompatibility, adherence, and dip time. (12th January 2023) - Griggs, Ryan; Karpman, Edward; Jones, LeRoy; Twomey, Carolyn; Henry, Gerard
Abstract: Background: Rates of infection after inflatable penile prosthesis range from 1% to 3%; however, a new surgical irrigation solution is Food and Drug Administration cleared as antimicrobial wound lavage and appears to be safe for patients and noncaustic during hydrophilic inflatable penile prosthesis (hIPP) dipping and irrigation. Aim: To evaluate if 0.05% chlorhexidine (CHG) lavage is caustic to the hIPP coating and if dip adherence is dependent on time. Methods: Preconnected hIPP devices were tested at a Coloplast research and development laboratory. The devices were soaked in the 0.05% CHG lavage solution or normal saline for 1, 15, 30, and 60 minutes. Subsequently, all parts were dried for 15 minutes in a 35 °C oven. A Congo red dye test was performed following a Coloplast-validated and Food and Drug Administration–cleared test method to ensure product reliability. Implants were then visually inspected for deleterious effects as well as dip coverage. In addition, we evaluated 0.05% CHG lavage solution vs previously published hIPP dipping solutions. Outcomes: 0.05% CHG lavage does not appear to damage the hIPP coating, and adherence of this solution is not dependent on dip time. Results: All components of the preconnected hydrophilic IPPs were tested for coating adherence and defects. All tested IPPs achieved a "satisfactory" coating, meaning a uniform coat without flaking or clumping. Furthermore, there were no noticeable caustic effects or differences in coating adherence between the normal saline–soaked control and 0.05% CHG–coated arms with increasing dip time. A review of the literature for 0.05% CHG lavage solutions vs previously published hIPP dipping solutions revealed that it may have some advantages over previously reported antibiotic solutions. Clinical Implications: This study serves as a foundation to introduce 0.05% CHG lavage to the urologic literature as a potentially new "magic bullet" irrigation. Strengths and Limitations: Major strengths of the study are that it is the first study of its kind to address the question of what dip duration should be used and whether it is scientifically reproducible. A limitation is the in vitro model, thus needing validation in a clinical setting. Conclusion: 0.05% CHG does not appear to negatively affect the hIPP coating or differ in adherence with increasing dip time; however, long-term device performance has not been verified.